Assessment of the Functional Capacity of the Elderly of Barangay San Fabian, Echague, Isabela - Edmelyn B. Cacayan; Kristel May B. Asuncion; Angelito Estoesta Alvarado (Health Notions, 2020)
Normal aging process, acute illness, worsening chronic illness, and hospitalization can contribute to a decline in the ability of the older adults to perform task necessary to live independently. One of the best way to evaluate the health status of the elderly is through functional assessment which provides data that may indicate future decline allowing the nurse and their primary care giver to intervene appropriately. This study was conducted to assess the functional capacity of the elderly living at San Fabian, Echague, Isabela. The Descriptive-Inferential design was used. A total of 107 respondents with a mean age of 70.26, majority are female (52.3%), married (62.6%), and obtained college education 29.9% and 10.3% are graduate and undergraduate respectively. 43% receives pension. Respondents and significant others were interviewed using a 3-point Likert scale. On the level of functional capacity, researcher found out that the elderly are independent in performing BADL and need assistance in performing of IADL such as ability to use phone, shopping, performing heavy domestic works, laundry, taking medication in correct time and handling of finances. Age has a negative significant relationship with their ability to perform both the BADL and IADL and there is a difference between gender and source of income and their ability to perform IADL. The study also shows a significant relationship between the respondent’s marital status and their education with their ability to do IADL. Keywords: functional capacity; elderly; assessment